Aspek Fonologi Dialek ‘Amiyah Mesir dan Konteks Sosial dalam Lagu Kontemporer: Analisis Sosiolinguistik Lagu Nafs El Haneen - Saputra, Mardan; Aeni, Prisilia Anghuril; Pribadi, Mohammad (Ta'limi | Journal of Arabic Education and Arabic Studies, 2026)
Arabic is a language characterized by a rich variety of dialects, in which everyday spoken varieties ('Amiyah) serve not only as a means of daily communication but also as markers of social and cultural identity. In contemporary Arabic popular music, the use of dialects is increasingly prominent, reflecting social intimacy and cultural representation. This study examines the phonological characteristics of the Egyptian 'Amiyah dialect and the social meanings represented in the contemporary song Nafs El Haneen by Tamer Hosny. Using descriptive qualitative methods within a sociolinguistic framework, this research aims to identify phonological differences between Egyptian 'Amiyah and Fusha Arabic and to explore how dialect features in lyrics reflect social and cultural values in modern Egyptian society. The findings reveal several phonological features characteristic of the Egyptian dialect, including the replacement of /q/ with /ʔ/, /ʤ/ with /g/, the omission of hamzah, and the simplification of diphthongs. Beyond its linguistic aspects, the song serves as a medium of emotional expression and cultural identity. The use of everyday dialect in popular music shows a shift from linguistic formality towards social closeness and emotional engagement, reinforcing local cultural identity in the context of globalization.